EXTENDED CULTIVATION TIME BEYOND 7 DAYS ENHANCES PROPIONIBACTERIUM ACNES ISOLATION IN SUSPECTED BONE AND JOINT INFECTIONS: A RETROSPECTIVE STUDY. - Deepti Kiran; Shambhu Prasad (Student's Journal of Health Research, 2023)
Background  Diagnosing bone and joint infections caused by Propionibacterium acnes is challenging due to the lengthy cultivation period, which can extend to 14 days. This study explored the potential of a 7-day cultivation period for precise diagnosis while maintaining sensitivity. Methods A one-year retrospective analysis included individuals with at least one positive Propionibacterium acnes sample. Patients were categorized as "infection" or "no infection" based on predefined criteria. The study assessed clinical and microbiological data, including time to positive results using different cultivation techniques. Results Among 70 confirmed P. acnes cases, the median time to positivity was 6 days, compared to 9 days in 47 contaminant cases. Tissue samples from 15 infected cases (21.4%) remained positive after day 7. Beyond day 10, blind thioglycolate broth subcultures detected infection in 6 patients (8.6%). Thioglycolate broth showed the highest sensitivity at 66.3%, while anaerobic agar plates had a notable positive predictive value of 96.5%. P. acnes growth occurred promptly upon transfer to the microbiological laboratory. Conclusion Reducing the cultivation period to 7 days may increase false-negative results by 21.4%. To achieve precise identification of P. acnes, it is recommended to implement a 10-day biopsy specimen culturing method for bone and joint infections, including a blind subculture. Recommendations Based on this study, it is advisable to conduct biopsy specimen culturing for 10 days, including a blind subculture after day 7, to accurately diagnose Propionibacterium acnes-related bone and joint infections. This approach enhances sensitivity and reduces the risk of false negatives. Further research and validation of this cultivation protocol may improve clinical diagnosis accuracy.